Apex-to-Cupola Distance Following VATS Predicts Recurrence in Patients With Primary Spontaneous Pneumothorax. Issue 37 (September 2015) - Chang, Jia-Ming; Lai, Wu-Wei; Yen, Yi-Ting; Tseng, Yau-Lin; Chen, Ying-Yuan; Wu, Ming-Ho; Chen, Wei; Light, Richard W.
Abstract : Abstract: Our study sought to determine whether the size of the residual apical pleural space in young patients with primary spontaneous pneumothorax (PSP) following video-assisted thoracoscopic surgery is associated with the risk of recurrence. We retrospectively reviewed patients (≤30 years' old) with primary spontaneous pneumothorax following thoracoscopic surgery (2002–2010) in a university-affiliated hospital. The size of residual apical pleural space was estimated by measuring the apex-to-cupola distance on a postoperative chest radiograph at 2 time windows: first between postoperative day (POD) 0 and 3, and second between POD 4 and 14. A total of 149 patients were enrolled with a median follow-up of 11.2 months (interquartile range, 0.95–29.5 months), of whom 141 (94.6%) were male with a mean age of 20 years. The postoperative recurrence rate was 11.4%. Comparing the characteristics between the patients with and without recurrent pneumothorax, the patients with recurrence were younger (18.2 + 2.4 vs 20.7 + 3.7 years, P = 0.008), with a lower rate of pleurodesis (35% vs1 69%, P = 0.037), longer apex-to-cupola distance at POD 0 to 3 (22.41 ± 19.56 vs 10.07 ± 10.83 mm, P < 0.001) and POD 4 to 14 (11.82 ± 9.75 vs 5.54 ± 8.38 mm, P = 0.005) than the patients without recurrence. In a multivariate logistic regression model for recurrent pneumothorax, age <18 years ( P = 0.026, odds ratio [OR]: 4.694), apex-to-cupola distance at POD 0 to 3> 10 mm ( P = 0.027, OR: 5.319), and no pleurodesis during VATS ( P = 0.022, OR: 5.042) were independent risk factors for recurrent pneumothorax. The recurrence rate was not low (11.4%) in young patients with PSP following VATS. Residual apical pleural space with apex-to-cupola distance of 10 mm or greater at POD 0 to 3, younger age, and no pleurodesis would increase postoperative recurrence of primary spontaneous pneumothorax.